A graphene ceramic lined heavy-duty anticorrosion coating and preparation method thereof

Through graphene ceramic lining heavy anticorrosion coating, the problem of ceramic lining is easily corroded during long-term use, achieving better anti-corrosion and hydrophobic effects, extending service life and reducing costs.

CN119081479BActive Publication Date: 2025-02-07甘肃衍河石油管道涂层有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411572754.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

During long-term use, the ceramic lining layer is easily scratched by particles in the flowing liquid and corroded in an alkaline environment, affecting its service life. The existing coatings have insufficient alkali resistance and hydrophobicity and are costly.

Method used

Use graphene ceramic inner lining heavy anticorrosion coatings, including graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder, maleic anhydride grafted polyethylene powder, titanate coupling agent modified magnesium oxide powder, etc., through static electricity The gun sprays and heats the knot to form a protective coating.

Benefits of technology

It improves the corrosion resistance of the ceramic lining layer, enhances the resistance to scratches of particulate matter, forms a better hydrophobic coating, extends the service life of the ceramic lining layer, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119081479B_ABST
    Figure CN119081479B_ABST
Patent Text Reader

Abstract

The invention discloses a graphene ceramic lining heavy anticorrosion coating and a preparation method thereof, which relates to the technical field of anticorrosion coatings, and comprises the following raw materials in parts by weight: 20 to 30 parts of graphene oxide modified polyethylene powder; 12 to 16 parts of ethylene acrylic acid copolymer powder; 6 to 8 parts of maleic anhydride grafted polyethylene powder; 20 to 30 parts of titanate coupling agent modified magnesium oxide powder; 0.5 to 0.7 parts of n-butyl titanate; 2 to 3 parts of tetramethyltetravinylcyclotetrasiloxane; and 1 to 1.5 parts of polyvinyl alcohol. The graphene ceramic lining heavy anticorrosion coating has good corrosion resistance, can further improve the anticorrosion effect of the ceramic lining surface, can prevent the surface of the ceramic lining layer from being scratched by particles, ensure the service life of the ceramic lining layer, can adhere to the ceramic lining layer more firmly, and the protective coating formed after sintering has better hydrophobicity and better anti-pollution and anti-oil effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a graphene ceramic lined heavy-duty anti-corrosion coating and a preparation method thereof. Background Art

[0002] In production activities such as transporting mud, limestone slurry and industrial wastewater, the liquid flowing in the pipeline is corrosive, which can easily cause serious corrosion of metal pipelines, increasing maintenance costs; therefore, in recent years, ceramic composite pipes have been used to replace other pipelines. Ceramic composite pipes are metal pipelines with ceramic linings. A smooth and hard ceramic layer is fired on the inner wall of the metal pipeline, which greatly improves the wear resistance and corrosion resistance of the pipeline, and correspondingly increases the service life of the pipeline.

[0003] However, during long-term use, the ceramic lining of the pipe is inevitably scratched by particles in the liquid flowing inside it. The scratched ceramic lining loses the protection of the glaze and will be gradually corroded in the alkaline liquid environment, thus affecting the service life of the ceramic lining.

[0004] In order to improve the anti-corrosion ability and protective effect of the ceramic lining layer, a coating layer is usually provided on the ceramic lining layer. The coating layer is mainly composed of phenolic resin, polyester resin and epoxy resin compounds as adhesive curing materials and mixed with fillers. However, phenolic resin and polyester resin coatings have poor alkali resistance, while epoxy resin coatings are expensive and have poor toughness. Moreover, the hydrophobicity of the coatings formed by the above two types of coatings needs to be improved, and they are easily contaminated by oil and form an oil layer. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A graphene ceramic lined heavy anti-corrosion coating, comprising the following raw materials in parts by weight:

[0006] 20-30 parts of graphene oxide modified polyethylene powder;

[0007] 12-16 parts of ethylene acrylic acid copolymer powder;

[0008] 6-8 parts of maleic anhydride grafted polyethylene powder;

[0009] 20-30 parts of magnesium oxide powder modified by titanate coupling agent;

[0010] 0.5-0.7 parts of n-butyl titanate;

[0011] 2-3 parts of tetramethyltetravinylcyclotetrasiloxane;

[0012] 1-1.5 parts of polyvinyl alcohol;

[0013] 10-12 parts of inorganic filler;

[0014] The particle size of the ethylene acrylic acid copolymer powder is 5 to 30 μm, and the particle size of the maleic anhydride grafted polyethylene powder is 5 to 30 μm.

[0015] The inorganic filler is titanium dioxide or white carbon black, and its particle size is 1 to 20 μm.

[0016] Also included: defoamers, isocyanates and antioxidants;

[0017] The above-mentioned antioxidant is hindered phenol antioxidant 1010 or hindered phenol antioxidant 1076.

[0018] The above-mentioned defoaming agent is benzoyl ketone.

[0019] Specifically, the preparation method of the graphene oxide modified polyethylene powder is as follows:

[0020] 5 parts by weight of high-density polyethylene powder with a radial size of 60 to 100 μm, 0.8 parts by weight of graphene oxide powder, 0.05 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite and 0.1 parts by weight of DL-411D aluminate coupling agent are prepared by ultrasonic dispersion, melt granulation, low-temperature ball milling, and sieving through a 30 μm sieve to obtain graphene oxide modified polyethylene powder.

[0021] The graphene oxide powder has a sheet diameter of 3 to 10 μm, a sheet number of 4 to 8 layers, and an oxidation degree of 40% to 55%.

[0022] In the above method, firstly, 0.8 parts by weight of graphene oxide powder is added into the container of ultrasonic dispersing mixer, then 0.05 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite and 0.1 parts by weight of DL-411D aluminate coupling agent are added, ultrasonic dispersing and stirring are performed for about 30 minutes, then 5 parts by weight of high-density polyethylene powder is added, ultrasonic dispersing and stirring are performed again for about 20 minutes, so as to make the above materials fully mixed and uniform; then, a powder material melting granulator is used, and the melting temperature is about 170 degrees to obtain flake or spherical particles with a particle size not greater than 5 mm, and after cooling, the particles are added into a low-temperature planetary ball mill, and the ball milling temperature is about -120°C. Among them, tris(2,4-di-tert-butylphenyl)phosphite is selected from Nanjing Milan Chemical, with a purity of 99% and a molecular weight of 589.

[0023] Specifically, the preparation method of the titanate coupling agent modified magnesium oxide powder is as follows:

[0024] a. Take 1 part by weight of QX-311W titanate coupling agent and 0.4 parts by weight of copper sulfate (copper sulfate pentahydrate), add to 4 parts by weight of pure water and stir evenly to prepare a mixed solution;

[0025] b. Mix 20 parts by weight of magnesium oxide powder with a particle size of 5 to 30 μm with 5 parts by weight of the mixed solution, disperse it ultrasonically for 50 minutes using an ultrasonic dispersing mixer, and then keep it at a constant temperature of 120° C. and a pressure of 0.6 MPa for 8 to 10 hours to obtain a titanate coupling agent modified magnesium oxide base material;

[0026] c. The obtained titanate coupling agent modified magnesium oxide base material is dried, crushed and sieved with a 30 μm sieve to obtain titanate coupling agent modified magnesium oxide powder.

[0027] The preparation method of the graphene ceramic lined heavy-duty anti-corrosion coating is as follows:

[0028] Step 1: Evenly mix 20 to 30 parts by weight of graphene oxide modified polyethylene powder, 12 to 16 parts by weight of ethylene acrylic acid copolymer powder, 6 to 8 parts by weight of maleic anhydride grafted polyethylene powder and 20 to 30 parts by weight of titanate coupling agent modified magnesium oxide powder to obtain composite powder A.

[0029] Step 2: Evenly mix ethanol and acetone in a mass ratio of 4:1 to obtain 20 parts by weight of a mixed solution, and then dissolve 0.5 to 0.7 parts by weight of n-butyl titanate, 2 to 3 parts by weight of tetramethyltetravinylcyclotetrasiloxane, a defoamer, triisocyanate and an antioxidant in the mixed solution to obtain a solution A.

[0030] In solution A, the amount of defoamer used is 0.5% to 0.7% of the sum of the mass of graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder and maleic anhydride grafted polyethylene powder, the amount of isocyanate used is 1% to 1.5% of the sum of the mass of graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder and maleic anhydride grafted polyethylene powder, and the amount of antioxidant used is 0.2% to 0.25% of the sum of the mass of graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder and maleic anhydride grafted polyethylene powder;

[0031] In step 2, the defoaming agent, isocyanate and antioxidant used must be soluble in ethanol or acetone. Ethanol and acetone are used as dispersion solutions. Since there are a small amount of dispersed graphene fragments on the particle surface of the graphene oxide modified polyethylene powder, they are easy to fall off in the subsequent stirring process and cause agglomeration. Adding acetone can disperse the graphene fragments and prevent the graphene fragments from agglomerating.

[0032] Step 3: Put the composite powder A and solution A into an electric stirring pot, stir at a temperature of 80°C to 90°C until they are dry, to obtain composite powder B.

[0033] Step 4: dilute 1 to 1.5 parts by weight of polyvinyl alcohol with 4 parts by weight of water, and then mix evenly with 10 to 12 parts by weight of inorganic filler, and then stir and dry at 105° C. to obtain a composite filler.

[0034] In step 4, the temperature of the dilution water is about 98° C. to ensure the solubility of the polyvinyl alcohol.

[0035] Step 5: Evenly mix the composite powder B and the composite filler, disperse by ultrasonic wave and sieve to obtain the finished product.

[0036] The finished product of the graphene ceramic lining heavy-duty anti-corrosion coating is a powder coating. When in use, it is sprayed on the ceramic lining surface by an electrostatic spray gun and heated and sintered at 135-140°C to form a protective coating.

[0037] The graphene ceramic lined heavy duty anti-corrosion coating has the following beneficial effects:

[0038] The graphene ceramic lining heavy-duty anti-corrosion coating has good corrosion resistance, can further improve the anti-corrosion effect of the ceramic lining surface, can prevent the surface of the ceramic lining layer from being scratched by particles, ensure the service life of the ceramic lining layer, and can adhere to the ceramic lining layer more firmly. The protective coating formed after sintering has better hydrophobicity, good anti-pollution and anti-oil effects, thereby further ensuring its anti-corrosion effect. In addition, its bonding base material is mainly polyethylene material, with low preparation cost. Compared with phenolic resin and epoxy resin coatings, polyethylene material itself has better toughness and alkali resistance, and can overcome the disadvantage of poor adhesion of polyethylene material to ceramic lining layer. It also has good adhesion at a low temperature of -20°C, so it has higher promotion value.

[0039] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a comparison chart of raw material dosage and test results of samples in test groups 1 to 6 of the present invention;

[0041] Figure 2 This is a finished product state diagram of the graphene ceramic lined heavy-duty anti-corrosion coating in the present invention. DETAILED DESCRIPTION

[0042] The present invention will be further described in detail below in combination with the relevant embodiments according to the technical solution of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1

[0043] 1. Test materials and sources:

[0044] Graphene oxide modified polyethylene powder: prepared by the preparation method of the technical solution of the present invention. Among them, high-density polyethylene powder was purchased from Dongguan Nabaichuan Plastic Chemical Co., Ltd., with a specification of 300-400 mesh; graphene oxide powder was purchased from Hebei Ruihuang Metal Materials Co., Ltd., with a specification of 300 nanometers to 10 microns; tris (2,4-di-tert-butylphenyl) phosphite was purchased from Nanjing Milan Chemical Co., Ltd.; DL-411D aluminate coupling agent was purchased from Shandong Nengju Chemical Co., Ltd.

[0045] Ethylene acrylic acid copolymer powder: the acrylic acid monomer content thereof is between 9% and 12%, and it was purchased from Dongguan Xinmiao New Materials Co., Ltd.

[0046] Maleic anhydride grafted polyethylene powder: purchased from Shanghai Yi Zeng Plastics Co., Ltd. The weight average molecular weight is between 3 million and 4 million, and the grafting rate is between 0.9% and 1.2%.

[0047] Titanate coupling agent modified magnesium oxide powder: prepared by the preparation method of the technical solution of the present invention, wherein QX-311W titanate coupling agent was purchased from Nanjing Quanxi New Materials Co., Ltd.; magnesium oxide powder was purchased from Hebei Yuechao Wear Resistant Materials Co., Ltd., with a specification of 5 to 20 μm.

[0048] n-Butyl titanate: purchased from Shandong Xinghai Chemical Co., Ltd., purity 99%.

[0049] Tetramethyltetravinylcyclotetrasiloxane: molecular weight is 344.66, purchased from Zhongshan Yuanda New Materials Co., Ltd.

[0050] Polyvinyl alcohol: high polymerization degree polyvinyl alcohol (molecular weight 170,000 to 220,000), purchased from Jinan Fangyu Chemical Co., Ltd.

[0051] The inorganic filler is titanium dioxide with a particle size of 5 to 50 μm.

[0052] The defoamer used was diphenylmethane, purchased from Hubei Shineng Chemical Technology Co., Ltd. with a purity of 99%; the isocyanate used was triphenylmethane triisocyanate purchased from Shandong Nengju Chemical Co., Ltd. with a purity of 99%; the antioxidant used was hindered phenol antioxidant 1076, purchased from Changzhou Youfeng Chemical.

[0053] The finished product of the graphene ceramic lined heavy duty anti-corrosion coating is a powder coating. Figure 2 shown.

[0054] 2. Test details:

[0055] Combined with the preparation method of the present invention, the powder coating prepared is sprayed on the ceramic lining test piece by an electrostatic spray gun, and after being heated at 138°C for 10 minutes for sintering and curing, the thickness of the cured coating is about 500μm, and the following performance test is carried out. Among them, the ceramic lining test piece adopts the ceramic coating test piece produced by Anhui New World Special Coatings Co., Ltd. The ceramic coating of the ceramic coating test piece is produced by the public technology of patent announcement number CN111793434B, and its surface characteristics are consistent with the surface characteristics of the mainstream ceramic lining in the market. The size and style of the test piece are formulated according to relevant test standards.

[0056] After spraying, the specimens of the graphene ceramic lined heavy anti-corrosion coating were subjected to the following performance tests. The test methods and test standards are as follows:

[0057] (1) Acid resistance test: Soak in 60% sulfuric acid solution at room temperature for 15 days.

[0058] (2) Alkali resistance test: Soak in 60% sodium hydroxide solution at 60 degrees Celsius for 15 days.

[0059] (3) Salt spray resistance test: Boil in pure boiling water at 100℃ for 8 hours, cool to room temperature and use FSG-N salt spray tester. The corrosion solution is 5% sodium chloride solution. The test temperature is set to 35℃ and the relative humidity is maintained at about 85%. The specimen is subjected to salt spray test for 1200 hours.

[0060] (4) Impact resistance test: GB / T 1732-1993 test standard is used for testing, and the average value is taken after 3 tests.

[0061] (5) Tensile bond strength test: According to the test standard of JC / T 547-2017 "Ceramic Tile Adhesive", the tensile bond strength between the coating and the smooth ceramic surface was tested, and the average value was taken after three tests.

[0062] (6) Hydrophobicity test: The coating samples were tested using the test standard GB / T 30693-2014 "Measurement of the contact angle between plastic film and water". The test equipment was a water drop projection contact angle measuring instrument. The contact angle was measured within 60 seconds after the water droplet was transferred. The contact angle was measured 3 times on the same sample and the average value was taken.

[0063] 3. According to the technical solution and preparation method of the present invention, the raw material (weight parts) ratio and test data are shown in Table A.

[0064] Table A:

[0065] Embodiment 2

[0066] On the basis of Example 1, the following test was carried out with the ratio of raw materials as a variable:

[0067] Table 1: Preparation materials and dosage of each test group

[0068]

[0069] Test Results

[0070] The performance test results of acid resistance, alkali resistance, salt spray resistance, impact resistance, tensile bonding strength and hydrophobicity of test groups 1 to 6 samples are shown in Table 2.

[0071] Table 2: Sample performance test results

[0072]

[0073] For the sake of comparison, test group 2 adopted the raw material ratio and experimental data of experimental group A in Example 1.

[0074] Test conclusion:

[0075] Combined with the preparation raw materials and dosage of test groups 1 to 6 in Table 1, and referring to the test results in Table 2, it can be seen that the graphene ceramic lining heavy anti-corrosion coating has good corrosion resistance and can further improve the anti-corrosion effect of the ceramic lining surface; its -20℃ impact resistance is as high as 43.5cm, and its 20℃ impact resistance is as high as 49cm, which can prevent the surface of the ceramic lining from being scratched by particles and ensure the service life of the ceramic lining; its -20℃ bonding tensile strength is as high as 33.1MPa, and its 20℃ bonding tensile strength is as high as 45.4MPa, which can adhere more firmly to the ceramic lining; in addition, the protective coating formed after sintering has a water contact angle of up to 135°, and has better hydrophobicity, so as to achieve better anti-pollution and anti-oil effects, thereby further ensuring its anti-corrosion effect.

[0076] In addition, the bonding base material of the graphene ceramic lined heavy-duty anti-corrosion coating is mainly polyethylene material, which has low preparation cost. Compared with phenolic resin and epoxy resin coatings, polyethylene material itself has better toughness and alkali resistance, and can overcome the shortcomings of poor adhesion of polyethylene material to the ceramic lining layer. It also has good adhesion at a low temperature of -20°C.

[0077] As attached Figure 1As shown, by referring to the raw material ratios of test groups 1 to 3 and test groups 4 to 6 in Table 1, and referring to the test results in Table 2, it can be seen that the graphene ceramic lining heavy-duty anti-corrosion coating, without adding any of the raw materials of n-butyl titanate, tetramethyltetravinylcyclotetrasiloxane and polyvinyl alcohol, will reduce the impact resistance and adhesion tensile strength of the coating. It can be seen that by adding n-butyl titanate, tetramethyltetravinylcyclotetrasiloxane and polyvinyl alcohol, the structural strength of the graphene ceramic lining heavy-duty anti-corrosion coating itself and the adhesion performance of the coating to the ceramic lining surface can be improved.

[0078] Control test and control conclusion:

[0079] 1. Based on test group 2, the following control test experiment was conducted:

[0080] Control group 1: 25 parts by weight of graphene oxide modified polyethylene powder were replaced with 25 parts by weight of high-density polyethylene powder of the same specification, and other raw materials and amounts remained unchanged.

[0081] Control group 2: 14 parts by weight of ethylene acrylic acid copolymer powder was replaced with 14 parts by weight of high-density polyethylene powder of the same specification, and other raw materials and amounts remained unchanged.

[0082] Control group 3: 7 parts by weight of maleic anhydride grafted polyethylene powder were replaced with 7 parts by weight of high-density polyethylene powder of the same specification, and other raw materials and amounts remained unchanged.

[0083] Control group 4: 25 parts by weight of the titanate coupling agent-modified magnesium oxide powder was replaced with 25 parts by weight of magnesium oxide powder of the same specification, and other raw materials and amounts remained unchanged.

[0084] The test results are shown in Table 3:

[0085] Table 3: Performance test results of control groups 1 to 4

[0086]

[0087] Comparative conclusion (I):

[0088] Through the comparative experimental results between the control group 1 and the test group 2, it can be seen that without adding graphene oxide modified polyethylene powder, the impact resistance of the graphene ceramic lined heavy-duty anti-corrosion coating in a low-temperature environment will be greatly reduced, and the hydrophobicity of the finished product surface will also be greatly affected.

[0089] Through the comparative experimental results between the control group 2 and the test group 2, it can be seen that without adding ethylene acrylic acid copolymer powder, the impact resistance and bonding tensile strength of the graphene ceramic lined heavy-duty anti-corrosion coating will be greatly reduced.

[0090] Through the comparative experimental results between the control group 3 and the test group 2, it can be seen that without adding maleic anhydride grafted polyethylene powder, it will also have a significant adverse effect on the impact resistance and bonding tensile strength of the graphene ceramic lined heavy-duty anti-corrosion coating.

[0091] Through the comparative experimental results of the control group 3 and the test group 2, it can be seen that the modified magnesium oxide powder can greatly improve the impact resistance of the graphene ceramic lined heavy-duty anti-corrosion coating.

[0092] Based on test group 2, the following control test experiments were conducted:

[0093] In control group 5 and control group 6, the 25 parts by weight of graphene oxide modified polyethylene powder was increased to 35 parts by weight and 40 parts by weight, respectively, and other raw materials and amounts remained unchanged.

[0094] Control group 7 and control group 8: 14 parts by weight of ethylene acrylic acid copolymer powder was increased to 20 parts by weight and 25 parts by weight respectively, and other raw materials and amounts remained unchanged.

[0095] Control group 9 and control group 10: the ethylene acrylic acid copolymer powder of 7 parts by weight was increased to 10 parts by weight and 12 parts by weight respectively, and the other raw materials and amounts remained unchanged.

[0096] The test results are shown in Table 4:

[0097] Table 4: Performance test results of control groups 5 to 10

[0098]

[0099] Comparative conclusion (II):

[0100] According to the comparative experimental results of control group 5, control group 6 and test group 2, when the addition amount of graphene oxide modified polyethylene powder is too much, it will have an adverse effect on the impact resistance and bonding tensile strength of the graphene ceramic lined heavy-duty anti-corrosion coating.

[0101] According to the comparative experimental results of control group 7, control group 8 and test group 2, when the addition amount of ethylene acrylic acid copolymer powder is too much, it will have an adverse effect on the hydrophobicity of the graphene ceramic lined heavy anti-corrosion coating.

[0102] According to the comparative experimental results of control group 9, control group 10 and test group 2, when the addition amount of maleic anhydride grafted polyethylene powder is too much, it will have an adverse effect on the bonding tensile strength and hydrophobicity of the graphene ceramic lined heavy anti-corrosion coating.

[0103] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A graphene ceramic lined heavy duty anti-corrosion coating, characterized in that: The preparation method comprises the following raw materials in parts by weight: 20 to 30 parts of graphene oxide modified polyethylene powder; 12 to 16 parts of ethylene acrylic acid copolymer powder; 6 to 8 parts of maleic anhydride grafted polyethylene powder; 20 to 30 parts of titanate coupling agent modified magnesium oxide powder, 0.5 to 0.7 parts of n-butyl titanate; 2 to 3 parts of tetramethyltetravinylcyclotetrasiloxane; 1-1.5 parts of polyvinyl alcohol; 10-12 parts of inorganic filler; Also included: defoamers, isocyanates and antioxidants; The preparation method of the graphene oxide modified polyethylene powder is as follows: 5 parts by weight of high-density polyethylene powder with a radial size of 60 to 100 μm, 0.8 parts by weight of graphene oxide powder, 0.05 parts by weight of tris(2,4-di-tert-butylphenyl)phosphite and 0.1 parts by weight of DL-411D aluminate coupling agent are prepared, subjected to ultrasonic dispersion, melt granulation, low-temperature ball milling, and then sieved through a 30 μm sieve to obtain graphene oxide modified polyethylene powder; The graphene oxide powder has a sheet diameter of 3 to 10 μm, a sheet number of 4 to 8 layers, and an oxidation degree of 40% to 55%. The preparation method of the titanate coupling agent modified magnesium oxide powder is as follows: a. Take 1 part by weight of QX-311W titanate coupling agent and 0.4 parts by weight of copper sulfate, add them into 4 parts by weight of pure water and stir evenly to prepare a mixed solution; b. Mix 20 parts by weight of magnesium oxide powder with a particle size of 5 to 30 μm with 5 parts by weight of the mixed solution, disperse it by ultrasonic for 50 minutes, and then keep it at a constant temperature of 120° C. and a pressure of 0.6 MPa for 8 to 10 hours to obtain a titanate coupling agent modified magnesium oxide base material; c. The obtained titanate coupling agent modified magnesium oxide base material is dried, crushed and sieved with a 30 μm sieve to obtain titanate coupling agent modified magnesium oxide powder.

2. The graphene ceramic lined heavy-duty anti-corrosion coating according to claim 1, characterized in that: The particle size of the ethylene acrylic acid copolymer powder is 5 to 30 μm, and the particle size of the maleic anhydride grafted polyethylene powder is 5 to 30 μm.

3. The graphene ceramic lined heavy-duty anti-corrosion coating according to claim 1, characterized in that: The inorganic filler is titanium dioxide or white carbon black, and its particle size is 1 to 20 μm.

4. The graphene ceramic lined heavy-duty anti-corrosion coating according to claim 1, characterized in that: The defoaming agent is benzoyl ketone.

5. The graphene ceramic lined heavy-duty anti-corrosion coating according to claim 1, characterized in that: The antioxidant is hindered phenol antioxidant 1010 or hindered phenol antioxidant 1076.

6. A method for preparing a graphene ceramic lined heavy-duty anti-corrosion coating, applicable to the graphene ceramic lined heavy-duty anti-corrosion coating according to claim 1, characterized in that: The steps include: Step 1: 20 to 30 parts by weight of graphene oxide modified polyethylene powder, 12 to 16 parts by weight of ethylene acrylic acid copolymer powder, 6 to 8 parts by weight of maleic anhydride grafted polyethylene powder and 20 to 30 parts by weight of titanate coupling agent modified magnesium oxide powder are uniformly mixed to obtain composite powder A; Step 2: Evenly mix ethanol and acetone in a mass ratio of 4:1 to obtain 20 parts by weight of a mixed solution, and then dissolve 0.5 to 0.7 parts by weight of n-butyl titanate, 2 to 3 parts by weight of tetramethyltetravinylcyclotetrasiloxane, a defoamer and an antioxidant in the mixed solution to obtain a solution A; In solution A, the amount of defoamer used is 0.5% to 0.7% of the sum of the mass of graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder and maleic anhydride grafted polyethylene powder, the amount of isocyanate used is 1% to 1.5% of the sum of the mass of graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder and maleic anhydride grafted polyethylene powder, and the amount of antioxidant used is 0.2% to 0.25% of the sum of the mass of graphene oxide modified polyethylene powder, ethylene acrylic acid copolymer powder and maleic anhydride grafted polyethylene powder; Step 3, putting the composite powder A and solution A into an electric stirring pot, stirring at a temperature of 80°C to 90°C until dry, to obtain composite powder B; Step 4: dilute 1 to 1.5 parts by weight of polyvinyl alcohol with 4 parts by weight of water, and then mix evenly with 10 to 12 parts by weight of inorganic filler, and then stir and dry at 105° C. to obtain a composite filler; Step 5: Evenly mix the composite powder B and the composite filler, disperse by ultrasonic wave and sieve to obtain the finished product.

Citation Information

Patent Citations

  • A method for preparing a high-temperature resistant ceramic anti-corrosion and heat-insulating coating

    CN111793434B

  • Environment-friendly insulating paint for non-oriented silicon steel and preparation method of coating thereof

    CN102634243A

  • Black ceramic additives, pigments and formulations

    CN106459665A